YsxC, a Putative GTP-Binding Protein Essential for Growth of Bacillus subtilis 168 - Prágai, Zoltán (American Society for Microbiology, 2000)
YsxC is a member of a family of GTP-binding proteins carried by a diverse range of organisms from bacteria to yeasts, plants, and humans. To resolve the issue of whether ysxC of Bacillus subtilis is essential for growth, we attempted to construct mutants in which ysxC was either inactivated or placed under the control of an inducible promoter. Viable mutants were obtained only in the latter case, and these were inducer dependent, demonstrating unambiguously that ysxC is an essential gene.